Single-centre real world experience of the Mynx Femoral closure device in patients undergoing percutaneous coronary intervention - S, Thirunavukarasu; M, Zaman; A, Hayat; R, Aghamohammadzadeh; N, Malik (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: Vascular closure devices are routinely used following femoral artery access to perform percutaneous coronary interventions (PCI). A number of devices are available on the market. We have reported previously on our experience of the Mynx device following diagnostic coronary angiography. Aims: To assess the success and complication rates of the Mynx device used in all-comers in the context of PCI within a single cardiac centre. Methods: Retrospective analysis of data available for patients who underwent PCI via the femoral route and received a Mynx device at a single tertiary centre. Results: The device was used to achieve haemostasis in 113 patients following PCI. In all cases weight-adjusted Heparin as well as dual antiplatelet therapy (Aspirin and Clopidogrel/ Ticagrelor) was administered as per PCI protocol. The device was successfully deployed in 111 cases (98.2%). The were 2 cases of device failure, one due to operator error and the other due to Mynx grip balloon bursting during device deployment. In 15 cases (13.2%; 9 male and 6 female) there were reports of small haematomas (<2cm) or oozing resulting in application of manual pressure or Femstop (St. Jude). A further patient required ultrasound-guided compression of the artery due to a large retroperitoneal bleed resulting from access complications. A larger proportion of the cases with complications were done as PPCI (44% vs 33%). The group with complications had higher systolic BP (140mmHg vs 128mmHg; P<0.05) and MABP (97mmHg vs 75mmHg; P<0.05) as compared with the group without any complications. Conclusion: The Mynx closure device is safe and easy to use in the context of PCI, in both the elective and emergency (PPCI) settings. Complication rates, predominately minor, can be minimised in experienced hands.